PENGARUH AROMATERAPI TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN DENGAN HIPERTENSI : LITERATURE REVIEW - Roswita, Ria (Jurnal Skala Kesehatan, 2022)
Abstract: Hypertension is a cardiovascular disease that causes the most death and is increasing every year. The prevalence of hypertension in Indonesia tends to increase in all provinces. One of the non-pharmacological hypertension interventions that can be done is aromatherapy. This study is a literature review that aims to determine the effect of aromatherapy on reducing blood pressure in hypertensive patients. This literature review analyzes 13 articles from journal databases, such as Google Schollar, Proquest and Science Direct with the keywords "aromatheraphy", "blood pressure" and "hypertension". The results of the analysis show that aromatherapy can lower blood pressure in patients with hypertension. In addition, the combination of aromatherapy with other interventions such as music therapy, meditation and deep breathing is also effective in lowering blood pressure in hypertensive patients. The results of this literature review are expected to determine the most effective dose and concentration in lowering blood pressure in hypertensive patients. Keyword : aromatherapy, hypertension, blood pressure.